Migration and Remittances in South Africa: the role of political factors - (:unkn) unknown (My University, 2011)
This paper looks at the determinants of international remittances in the case of South-South migrations. Using micro-economic data from a survey conducted in 2006, analysis was carried out on 639 African migrants residing in Johannesburg. Besides the traditional variables (income, household’s size in the host country, age, sex, education…), political variables (regime change in the host country and conditions in the country of origin before the migration including war, and conflict) are used in the analysis. The results highlight the importance of these political variables as determinants of migrants’ probability to remit. The end of the apartheid regime in South Africa impacts positively and significantly the probability of remitting money to the home country while the fact of having fled one’s country of origin because of violence or conflict has the opposite effect. However, the political change in the host country has no influence on the amounts transferred. Once the decision to remit is taken, traditional variables have more of an explanatory power in predicting amounts transferred than political variables.
Keywords: African Research